AN EMPIRICAL INVESTIGATION OF FACTORS AFFECTING PASSENGER’S REPURCHASE INTENTION TOWARDS LOW-COST AIRLINE IN THAILAND - Thanalerdsobhon, Kathabhon; Chaipoopirutana, Sirion (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
With the economic situation at this time, being able to generate some profits for the airlines is difficult. However, to be able to survive in this changing world is harder. As there are many competitions in the aviation industry in Thailand. Airlines are competing with one another either by price promotion, or cost. Many factors are affecting the world’s economy right now. For example, economic war between the united states of America and China, the appreciation of Thai Baht, the political problems, and others to be able to survive in this crisis, creating the factor of repurchase intention would be the solution to all the airlines. The motive of the study is to investigate the influence of affecting factors: service quality in terms of tangible factors, schedule factors, service provided by ground personnel, service provided by flight attendants, trust, brand image, perceived value, and customer satisfaction on repurchase intention towards one particular budget-airline in Thailand. The researchers gathered data from real passengers of the low-cost airline at Don Mueang International Airport and Suvarnabhumi Airport, Thailand. The sample size of this study is 409 respondents. The data is collected by the questionnaire distribution. Descriptive research with quota sampling, judgement sampling, and convenience sampling under non-probability was applied. The five Liker-scale was used to help with the research instrument. The researchers applied descriptive and inferential analysis methods to complete the process. Besides, the Multiple Regression Linear was adopted to help test all the hypotheses. Based on the findings, the researchers found that service quality in terms of tangible factors, service provided by ground personnel, and service provided by flight attendants, trust, brand image, perceived value and customer satisfaction statistically have an influence on repurchase intention. Keywords: service quality, trust, brand image, perceived value, customer satisfaction, and repurchase intention.